Perceptions of Senior High School Students and Teachers on the Course Introduction to Philosophy of the Human Person - Telan, Jomabier (JPAIR Multidisciplinary Research, 2019)
The course Introduction to Philosophy of the Human Person is relatively new. Unlike other courses in the fields of Humanities, Sciences, and Mathematics which were also offered in the Senior High School Program, no formal research has been made in order to fortify or assess its utility and efficacy. Truly, the implementation of the Senior High School in June 2016 brought an utter change in the Philippine educational system. It was also expected that problems and issues arose from it. Thus, this study aimed to know the perceptions of nine (9) Senior High School students and two (2) Senior High School teachers on the course Introduction to Philosophy of the Human Person. The participants were selected through quota sampling. Their personal experiences and point of views on the course are of great importance in this study. So, to deeply extract the data, the researcher used a qualitative-phenomenological design. Personal interview and focus group discussion were the means to get the data from the participants. The findings include: (a) Good implications of the subject; (b) Issues raised by the teachers; (c) and problems encountered by students and teachers. Hence, the students and teachers in this study did find good implications, issues, and problems in the course Introduction to Philosophy of the Human Person.
Keywords: Philosophy; perception; Introduction to Philosophy of the human person; qualitative; phenomenological design